Mechanics of materials (McGraw-Hill Higher Education, 2009)
This text: is designed for the first course in mechanics of materials - or strength of materials - offered to engineering students in the sophomore or junior year. The main objective is to help develop in the engineering student the ability to analyse a given problem in a simple and logical manner and to apply to its solution a few fundamental and well-understood principles. In this text, the study of the mechanics of materials is based on the understanding of a few basic concepts and on the use of simplified models. This approach makes it possible to develop all the necessary formulas in a rational and logical manner and to clearly indicate the conditions under which they can be safely applied to the analysis and design of actual engineering structures and machine components. Features of this title include new and revised problems as well as Hands-On Mechanics which helps the professor build in-class experiments that demonstrate complicated topics in the text.